Предмет: Алгебра, автор: ЕлиzаветA

х (х2   -2) = х3 +8

Ответы

Автор ответа: Vladislavoch
0
  2х=3х+8                                                                                                                     2х-3х=8                                                                                                                     -1х=8                                                                                                                           х=8:(-1)=-8                         
Похожие вопросы